Cost Leadership Strategy and Differentiation Strategy Mediate the Effect of Entrepreneurship Orientation on the Performance of Batik Lendah SMEs - Yanuar Prima; Sabihaini Sabihaini; Abdul Ghofar (Jurnal Manajemen Dan Kewirausahaan, 2022)
Batik SMEs in Lendah District are facing business challenges during the pandemic. The challenge is the decline in sales of batik cloth. The decline in sales of batik cloth has an impact on the performance of Batik SMEs in the Lendah District. Performance is the achievement of specified organizational goals. The purpose of this research is to look at cost leadership strategies and differentiation strategies as a mediation of entrepreneurial orientation and performance in Batik Lendah SMEs, Kulon Progo. This research includes quantitative research with a survey method to 55 owners/managers of Batik SMEs in Lendah District. Data collection using a questionnaire and analyzed using SmartPLS 3.0. The results show: 1) entrepreneurial orientation had a significant positive effect on performance, 2) entrepreneurial orientation had a significant positive effect on cost leadership strategy, 3) entrepreneurial orientation had a significant positive effect on a differentiation strategy, 4) cost leadership strategy had a significant positive effect on performance, 5) differentiation strategy has a significant positive effect on performance, 6) entrepreneurial orientation and performance can be mediated by the application of cost leadership strategy, 7) entrepreneurial orientation and performance can be mediated by differentiation strategy.